2014
DOI: 10.1002/ccd.25700
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of secundum atrial septal defects not percutaneously closed

Abstract: Objectives We sought to review our single center experience with secundum atrial septal defect (ASD) device closure, evaluating the incidence and morphological characteristics where percutaneous closure was thought inappropriate. Material and methods All children assessed as unsuitable for transcatheter device closure were reviewed. Data collected included: demographics, defect morphology by echocardiogrphy or at cardiac catheterization and defect size focusing on the reasons for procedural deferral. Results B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Percutaneous ASD device closure has become a standard option for asymptomatic older children and adults with secundum ASD [11]. However, its indication in infants and small children may be limited because of underlying ASD anatomy (defect too large, sinus venosus type or primum type ASD, deficient rim, multiple defects, and aneurysmal septum), small left atrium, and small size of an access vessel [12][13][14]. Surgical ASD closure is frequently indicated for those who are not amenable to the device closure and those who are clinically deteriorating despite maximum medical support, especially in infants and young children with known comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous ASD device closure has become a standard option for asymptomatic older children and adults with secundum ASD [11]. However, its indication in infants and small children may be limited because of underlying ASD anatomy (defect too large, sinus venosus type or primum type ASD, deficient rim, multiple defects, and aneurysmal septum), small left atrium, and small size of an access vessel [12][13][14]. Surgical ASD closure is frequently indicated for those who are not amenable to the device closure and those who are clinically deteriorating despite maximum medical support, especially in infants and young children with known comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patient weight can be used as a guide for device size selection. The criteria proposed that device diameter (in mm) to weight (in kg) ratio should be less < 1.5 [18]. In the current study, multivariate analysis showed that the device waist diameter in relation to the height of the patients seems to be statistically more important than its relation to weight.…”
Section: Predictors Of Procedures Prolongationmentioning
confidence: 46%
“…A deficient rim is defined as less than 5 mm. 64 The deficient retroaortic rim is present in 36% to 57% of patients with secundum ASD. 65 It was shown that percutaneous closure of ASD with the absent or deficient retroaortic rim is the cause of an increased risk of erosion, but most leading centers treat these patients percutaneously.…”
Section: Short Review Of the Devices Available Inmentioning
confidence: 99%